Strain differentiation of Mycobacterium tuberculosis for epidemiology in northwest of Iran - Asgharzadeh, M; Samadi Kafil, H; Pourostadi, M; Asadi Faezi, N; Rashedi, J; Mahdavipour, B (Cellular and Molecular Biology, 2016)
Tuberculosis is a major health problem throughout the world and there are still a great number of people with the disease. Planning for controlling tuberculosis is required to identify the sources of infection and screening for the disease. The aim of this study is the differentiation of Mycobacterium tuberculosis strains for better understands the spread of the disease in North West Iran. In this study, 194 positive cultures of M. tuberculosis in North West Iran were evaluated by the MIRU-VNTR method. MIRU-12 differentiated the 194 isolates into 138 different patterns, comprising 30 clusters and 108 unique patterns (HGDI=0.9930). The largest cluster contained twelve isolates. The results showed that the majority of TB cases in North West Iran are due to reactivation and the 12-MIRU typing method can be used as a first-line method for strain differentiation of M. tuberculosis.